A search for the tyrosinase-positive oculocutaneous albinism gene using linkage analysis. - Kedda, Mary-Anne (My University, 1993)
Tyrosinase-positive oculocutaneous albinism (ty-pos OCA) is an autosomal recessive disorder of the melanin pigmentary system, characterised by generalised hypopigmentation, with the accumulation of phacomelanin pigments with increasing age. Southern African ty-pos OCA individuals occur with two distinct phenotypes? with or without ephelides. These phenotypes are apparently concordant within families, suggesting that there is more than one mutation at the ty-pos OCA locus. Elucidation of the basic defcct{s) in ty-pos OCA would be aided by a definitive localisation of the ty-pos OCA gene. Linkage studies have been carried out in 41 families, using 52 markers, including 15 random polymorphic serogenetic markers and 16 random polymorphic DNA markers, as well as markers from two candidae, genes, TYR and CAS2, and 19 polymorphic markers from 2 candidate chrome somal regions, on 11p and 15q. Pairwise 100 scores were calculated using the MLINK program of the LINKAGE package. A • significant lad score was initially obtained in linkage analysis between ty-pos OCA and two chromosome 15qll-q13 markers, in the Prader-Willi/Angelman Syndrome (PWS/AS) region. Linkage analysis with 13 other markers on chromosome 15, confirmed this localisation. A genetic linkage map of the proximal region of the long arm of chromosome 15 was constructed and shows that the most closely linked, flanking loci are the GABRB3 and D1SS24. Linkage analysis has also shown no cross-overs between the D15S12 locus and ty-pos OCA in southern African Negroids, suggesting that this locus is very close to, or part of, the disease locus. Caucasoid "ty-pos" OCA individuals are characterised by locus heterogeneity. Negroid ty-pos OCA families with and without ephelides were analysed separately at the tyrosinase and D15S12 (PIRlO-l) loci. The summated 100 scores at 9=0.01 were negative for the tyrosinase locus and positive for the D15S12 locus, suggesting no evidence for locus heterogeneity in this population. Allelic association was found between the polymorphic alleles detected at the D15S12 (PIRIO-l) locus and ephelus status, which suggests th~t there were multiple origins of the mutations at tne ty-pos OCA locus, The results of this thesis show that the ty-pos OCA gene is located on chromosome ISq 11~ q12. The gene is postulated to be the human homologue, P, of the mouse pinkeyed dilution gene, p; although definitive proof awaits the detection of mutations in this gene in individuals with ty-pos OCA.
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Albinism, Oculocutaneous.